Genetic Variation of the DGAT1 gene in Dual-Purpose Dairy Cows and its Influence on Economically Important Breeding Traits - Mark E Armitage; Emma Swan; Denise O'Meara (SURE Journal: (Science Undergraduate Research Experience Journal))
BackgroundOver the last 10 years, the discovery of individual, or candidate, genes that influence economically important traits has revolutionised how the dairy industry selects cows for breeding programmes. One such gene, the diacylglycerol O-acyltransferase 1 (DGAT1) gene is significant in dairy production as it is associated with the synthesis of fat in milk, and polymorphisms within the gene can be used for selection purposes. In this study, the variants (genotypes) of the K232A polymorphism of the DGAT1 gene, within a dual-purpose dairy herd, bred for both dairy and beef production, were determined, and compared to the Economic Breeding Index (EBI) and EBI sub-indexes to ascertain if any statistically significant relationships existed. MethodsDNA was extracted from hair samples, and the genotypes of the DGAT1 gene were determined using a combination of conventional PCR, restriction fragment length polymorphism (RFLP), gel electrophoresis, DNA sequencing and novel real-time PCR assays. ResultsThe three genotypes within the herd were: KK (n = 5), AA (n = 10), KA (n = 8). KK denoted a homologous Lysine allele, AA denoted a homologous Alanine allele, and KA denoted a heterologous Lysine allele. There was no association found between the milk production traits and the DGAT1 K232A genotype (P = 0.178). However, there was a significant association found between the K232A polymorphism and other EBI traits including ‘Beef’ and ‘Management’ which had P values of 0.035 and 0.023 respectively. The AA genotype was associated with higher beef traits (higher carcass values) and lower management traits (reduced milking time and good temperament). The KK genotype was associated with higher management traits and lower beef traits. These results were not always consistent with those in the literature. ConclusionsThis study showed that animals with the A allele of the DGAT1 gene polymorphism may be better suited for dual-purpose dairy herds. It is also possible that different breeding goals and farm environments may influence the results suggesting that these types of studies should be conducted on a variety of herds and include larger samples sizes.